Tantangan Pelestarian Pembelajaran Bahasa Arab Santri Pondok Pesantren Nahdlatul Ulum - Nahdla, Naila Cahya; Munawar, Endang (Al Maghazi : Arabic Language in Higher Education, 2024)
This research aims to identify and discuss effective strategies in overcoming various obstacles that arise in the process of preserving Arabic language learning for students at the Nahdlatul Ulum Metro Islamic Boarding School. This type of research is descriptive qualitative research. Data was collected through interviews and observations, the data obtained was processed using the following procedures; Data reduction; by analyzing systematically by identifying patterns and relevant information, displaying data to make the data easier to understand, and providing a clearer view of the research results. and Data verification which involves double-checking the accuracy of the data and findings obtained by this research to produce and provide various strategies that are relevant, adaptive and effective for Arabic language teachers in the learning process in the world of education related to life in Islamic boarding schools and current developments. The researcher hopes that this research can add to knowledge and contribute ideas to optimize the efforts of an Islamic boarding school institution in preserving and quality of learning, especially for Arabic language students, and it is hoped that it can increase professionalism in teaching so that the goals in learning Arabic can be achieved well and efficiently.